PUBLIC POLICY STUDY BASED ON HUMAN DEVELOPMENT INDEX THROUGH THE STRATEGIC ROLE OF GP ANSOR BONDOWOSO - Raziqi, Ahmad; Sholihah, Dawimatus; Umam, M. Syafiqil (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Human Development Index (HDI) is widely recognized as a key metric for assessing the overall quality of human development. Based on data provided by the Central Bureau of Statistics (BPS), the HDI of Bondowoso Regency increased from 66.75 in 2023 to 71.22 in 2024. This study adopts a qualitative approach to examine the strategic role of GP Ansor Bondowoso in supporting public policies aimed at improving HDI outcomes. The findings reveal three key insights. First, there exists a collaborative governance framework between the local government and GP Ansor Bondowoso, facilitating joint efforts in policy implementation. Second, GP Ansor Bondowoso effectively leverages the Capability Approach to address multidimensional aspects of human development. Third, the organization functions as a civil society actor with substantial public trust capital, enabling it to mediate between government policies and community aspirations. This study contributes to the literature by highlighting the role of faith-based civil society organizations in strengthening public policy performance, enhancing human development outcomes, and reinforcing social capital within the governance ecosystem.